Warsaw’s history of II World War through the eyes of three Hungarian journalists and writers - Grad, Marcin (City and War, 2021)
This article is an overview of Warsaw’s history during the II World War, presented in the pages of three Hungarian reportages: György Somlyó’s A Visztula sellője. Lengyelországi útinapló (The Vistula’s Mermaid. A journal from journey across Poland), Tibor Pethő’s A Kárpátoktól a Balti-tengerig (From the Carpathians to the Baltic) and Péter Ruffy’s Varsói hajnal (Varsovian dawn). Those books are results of visits of the above-mentioned journalists and writers from Hungary. Somlyó, Pethő and Ruffy were in Poland (including Warsaw) in the 1950s, when the memory of cataclysm of the II World War had been still very vivid, yet in the capital the traces of war were still visible. In the Hungarian authors’ reports about history of Warsaw during the years of the II World War, presentation of two uprisings – Warsaw Ghetto Uprising in 1943 and Warsaw Uprising in 1944 (to be precise, it should be noted, that György Somlyó barely writes anything about the latter, which could be politically and ideologically motivated) – occupies an important place. The picture of Varsovian war history presented in the pages of A Visztula sellője, A Kárpátoktól a Balti-tengerig and Varsói hajnal completely fits polish after-war political and historical narrative, in some parts (e.g. regarding Warsaw Uprising) it is also marked by propaganda. In spite of these „drawbacks”, at the time the presented reportages surely contributed to the increasing knowledge of Hungarian readers about the events of II World War in Warsaw and generally in Poland, yet about the after-war rebuild of the country, which, due to the limits concerning volume of texts, will not be included in this article.